A pre-planning for hotel locating according to the sustainability perspective based on BWM-WASPAS approach - Hashemkhani Zolfani, Sarfaraz; Mosharafiandehkordi, Sepideh; Kutut, Vladislavas (International Journal of Strategic Property Management, 2019)
Finding an appropriate location from any kind of perspectives is a really vital issue for businesses. Searching for the best location to meet a business perspective which can be also a sustainable one would be really challenging and it needs pre-planning. Locating for business issues in tourism industry for instance hotel locating is one of the major complicated topics in this area. Locating can come along with pre-planning and kind of feasibility studies which can cover all necessities of current and future needs of an issue. Locating with sustainability point of view is one the newest approach in different studies which this research is also working on that based on a hybrid Multiple Attribute Decision Making (MADM) model. MADM methods are really suitable ways in making complicated decisions in different areas. A hybrid MADM model based on BWM-WASPAS is applied for locating problem in finding the best location for the hotel locating challenge. To meet the aim of this research, a case study for evaluating probable locations of a five star hotel examined for the Shahrekord city, Iran. As locations were prioritized based on sustainability perspective, business goals can also be seen as a pre-planning project.